Prospective randomized study of stress and immune response after laparoscopic vs conventional colonic resection - Kuntz, Christian; Wunsch, A.; Bay, Fatma; Windeler, Jürgen; Glaser, Florian; Herfarth, Christian (Surgical endoscopy and other interventional techniques, 1998)
Methods: In order to evaluate the stress and immunological response to laparoscopic and conventional colon resection we operated on male Wistar rats (350-380 g), performing either laparoscopic (n= 15) or open colon resection (n= 15). A third group (n= 10) underwent anesthesia only. Immediately before and after surgery as well as 1 and 7 days postoperatively a 1 ml sample of blood was taken from the retrobulbar veinous plexus. Stress (corticosterone) and immune parameters (neopterin and interleukin [IL] 1-β) were measured. Furthermore, the body weight as a parameter of postoperative recovery was monitored.
Elektronische Reproduktion der Druck-Ausgabe 29. April 2014
Gesehen am 30.10.2025